Quantification of internal training load in professional players of futsal - Ibáñez Pérez, R. J.; Huerta López, G.; Juan Meroño, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
The objective was to know the existing differences in how the intensity of training affects professional futsal players, taking into account the position occupied on the pitch, and compare the heart rate parameters between training and competition. The investigation was carried out to the Romero Cartagena F.S. Plastics team, recording the maximum heart rate means with heart rate monitors and the collection of the Subjective Perception of Effort, through the Borg scale. The results obtained did not show significant differences with respect to the quantified load in the three positions, in addition the internal load manifested itself in a more demanding way in players who occupied the position of “Wing” and “Pivot”. The heart rate parameters recorded in training were very distant from the competition data collected by other studies and the subjective perception of effort was shown as a valid method for the quantification of the load.